Recent Progress on Redox Materials for High‐Temperature Thermochemical Heat Storage - Alfonso J. Carrillo; José Manuel Serra (Advanced Energy & Sustainability Research)
Thermal energy storage based on gas–solid reversible chemical reactions offers higher‐energy storage densities than commercially implemented sensible heat‐storage systems. Despite the promise, it is a much less mature technology, and several aspects still require further improvement. Among the wide variety of reversible thermochemical reactions that show potential for thermal energy storage, reduction–oxidation reactions of metal oxides are promising since air can be employed as reactant without the need of costly pressurized storage units. In this perspective, the fundamental aspects of metal oxides for redox thermochemical heat storage are explored, paying special attention to the latest developments that will assure high energy‐storage density and multicycle stability. The design of more efficient redox materials remains a key aspect in thermochemical heat storage; however, the development of high‐temperature reactors and their implementation in concentrated solar power plants also plays an important role in the advancement of this technology. All these interrelated elements together with techno‐economic assessments, a paramount tool in terms of materials choice, are also discussed.